Synthesis of Ultrastable Ag Nanoplates/Polyethylenimine–Reduced Graphene Oxide and Its Application as a Versatile Electrochemical Sensor. Issue 31 (30th June 2016) - Wang, Jindi; Zhang, Guoxin; Sun, Wanxia; Sun, Jingsong; Luo, Liang; Chang, Zheng; Sun, Xiaoming
Abstract: Investigations on Ag nanostructures/reduced graphene oxide composites have been frequently reported, yet the morphology control of those loaded Ag nanocrystals is still challenging. We herein develop a facile method to grow triangular Ag nanoplates (AgP) on polyethylenimine‐modified reduced graphene oxide (AgP/PEI‐rGO). The AgP/PEI‐rGO hybrids show unexpected high stability against chloride ions (Cl − ) and hydrogen peroxide (H2 O2 ), which is possibly due to the strong interaction between surface Ag atoms with the amine groups of PEI. In the chronoamperometry measurements for detecting H2 O2, N2 H4, and NaNO2, the AgP/PEI‐rGO hybrid shows very wide linear ranges (usually 10 −6 –10 −2  mol L −1 for H2 O2, N2 H4, and NaNO2 ) and low detection limits (down to ≈1×10 −7  mol L −1 ), which demonstrate the promising electrochemical sensor applications of these metal/graphene hybrids with well‐defined morphologies and facets. In addition, this strategy could be extended to the deposition of other noble metals on rGO with controlled morphologies. Abstract : Ultrastable hybrids : Ag nanoplates/polyethylenimine‐modified reduced graphene oxide (AgP/PEI‐rGO) hybrids show unexpected higher stability against Cl − and H2 O2 than either AgP or mixtures of PEI‐rGO and AgP. The AgP/PEI‐rGO hybrids show very wide linear response ranges and low detection limits in the electrochemical detection of H2 O2, N2 H4, and NaNO2 (see scheme).